Question And Answer Controller Composition (Qacc): A Technique for Developing Students’ Writing Skill - Rekha Asmara (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2015)
Abstract: This study aimed at investigating whether or not there was a significant difference in writing achievement between the students who were taught by using Question and Answer Controller Composition (QACC) technique and that of those who were not. A quasi-experimental method was conducted toward the eleventh grade students in Senior High School YPPG Tanjung raja in which forty-two students were involved as the sample which was divided into two groups. In collecting the data, a written test was administered. Before giving the test, the test was tried out to non-sample students in order to know its validity and reliability. Then, the data were analyzed using t-test through SPSS 16. The result showed that t-obtained was 4.788 at the significant level 0.05 and the critical value of t-table was 2.0211. Since t-obtained (4.788) was higher than t-table (2.0211) and pvalue (0.000) was less than αvalue (0.002), it could be concluded that the null hypotheses (Ho) was rejected and the research hypotheses (Ha) was accepted. In other words, there was a significant difference in writing achievement between the students who were taught by using Question and Answer Controller Composition (QACC) technique and that of those who were not. Key words: Question and Answer Controller Composition technique, report writing